1993
DOI: 10.1016/0014-5793(93)81349-5
|View full text |Cite
|
Sign up to set email alerts
|

Mobility in pyruvate dehydrogenase complexes with multiple lipoyl domains

Abstract: High-field NMR studies were carried out with genetically-reconstructed pyruvate dehydrogenase (PDH) complexes of Escherichia coli containing from zero to nine lipoyl domains per lipoate acetyltransferase (E2p) subunit. The only significant differences between the NMR spectra were the increasing intensities of the signals derived from the lipoyl domains and their associated linkers, and the much enhanced signal from the E3-binding domain and its linker in complexes that are devoid of lipoyl domains. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This is apparent from the impairment that accompanies the shortening or replacing of the residual lipoyl linker of a llip-PDH complex, and the enhancement afforded by incorporating a polyproline linker (Miles et al, 1988 ;Turner et al, 1993). High-field H1-NMR studies with variants containing from zero to nine lipoyl domains per E2p chain gave the first indication that the mobility of the lipoyl linkers relative to the domains, and hence the catalytic efficiency, is highest in the wild-type complex (Machado et al, 1993). The superiority of the 3lip-PDH complex has since been confirmed in physiological studies with stable isogenic strains that express llip-, 21ip-and 3lip-PDH complexes, in which it was concluded that lowering the lipoyl domain content adversely affects growth rate and yield (DavC et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…This is apparent from the impairment that accompanies the shortening or replacing of the residual lipoyl linker of a llip-PDH complex, and the enhancement afforded by incorporating a polyproline linker (Miles et al, 1988 ;Turner et al, 1993). High-field H1-NMR studies with variants containing from zero to nine lipoyl domains per E2p chain gave the first indication that the mobility of the lipoyl linkers relative to the domains, and hence the catalytic efficiency, is highest in the wild-type complex (Machado et al, 1993). The superiority of the 3lip-PDH complex has since been confirmed in physiological studies with stable isogenic strains that express llip-, 21ip-and 3lip-PDH complexes, in which it was concluded that lowering the lipoyl domain content adversely affects growth rate and yield (DavC et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, as noted in the Introduction, some roles require assembled E2 structures. Guest and colleagues have characterized a variety of assembled E. coli PDC-E2 structures for lipoyl domain roles and found the three lipoyl domains have equivalent capacities in supporting the overall PDC reaction (67)(68)(69). As in the case of S. cerevisiae PDC (27), production of mammalian E2 free of E3BP is important for distinguishing the contribution of these two lipoyl-bearing components in catalytic and regulatory processes.…”
mentioning
confidence: 99%
“…High-field NMR studies were carried out with variants containing zero to nine lipoyl domains per E2p subunit. These studies suggest an explanation for the presence of three lipoyl domains per E2p subunit in the wild-type PDH complex that is based on the greater inherent mobility and thus potentially more efficient active-site coupling of this arrangement (170). The superiority of the three lipoyl domain-PDH complex has since been confirmed by physiological studies from which it was concluded that decreased lipoyl domain contents adversely affect growth rate and growth yield (171).…”
Section: Structures Of Lipoylated and Biotinylated Proteinsmentioning
confidence: 87%